Immunogenicity and Efficacy of Heat Inactivated Whole-Cell Vaccine to Increase Murine Survival after Extensively Drug-resistant Acinetobacter baumannii Infection - Sharmin, Nazmun; Khoda, Md Mahbub E; Uddin, Mohammad Nazim (International Journal of Human and Health Sciences (IJHHS), 2024)
Background: Due to the rapid emergence of extensively drug-resistant strains of Acinetobacter baumannii worldwide, there is a necessity for greater consideration of the role of preventive vaccines in combating these pathogens. Objective: The study aims to assess the effectiveness of a heat-inactivated whole-cell vaccine against A. baumannii. Methods: Eleven Swiss albino mice were divided into Experimental (n=4), Placebo-controlled (n=4), and Negative Control (n=3) Groups. Clinically isolated extensively drug-resistant A. baumannii species emulsified wih Complete Freund’s adjuvant was used for intramuscular vaccination in the Experimental group in three different phases on 14-day intervals whereas the Placebo-controlled group received phosphatebuffered saline emulsified with CFA in the same schedule and Negative Control group was kept unimmunized. Serum was collected from the tail blood of each mouse on the 10th day after each immunization, by cardiac puncture on the 14th day after the lethal dose from the experimental group, and after the death of the placebo-controlled group. Results: Mice inoculated with heatinactivated whole-cell vaccine survived and showed a higher neutralizing (IgG) antibody response after 2nd (>7-fold titer) and 3rd inoculation (>12-fold titer) whereas all mice from the Placebocontrolled group and Negative Control group did not survive after lethal challenge with different extensively drug-resistant strain of A. baumannii. Sera from the experimental group of mice collected after 3rd inoculation resulted in a higher serum bactericidal killing index after three hours of incubation. Conclusion: These results suggest intramuscular vaccination with heat-inactivated whole-cell vaccine survival after extensively drug-resistant A. baumannii infection. International Journal of Human and Health Sciences Vol. 08 No. 03 Jul’24 Page: 275-282